A study on the etching characteristics of atmospheric pressure plasma for single-crystal silicon wafer. (August 2021) - Guo, Weijia; Michael M Calija, Laurence; Xu, Peng; Liu, Kui; Kumar A, Senthil
Abstract: Atmospheric-pressure (AP) plasma sources have attracted researchers in many engineering fields, due to its low cost and easy handling. The AP plasma technique has been successfully applied on the surface figuring and texturing of Si, fused silica, RS-SiC, and SiC, etc. However, these studies focus more on better control for surface figuring of the substrate. The understanding of how the Si surface roughening or smoothing is occurred during the AP plasma etching using He-based CF4 mixture gas has seldom been reported. The present study starts from a parametric study of O2 addition concentration to He-based CF4 plasma. A groove is initially etched on a single-crystal silicon wafer by the CCP-type parallel-plate plasma etcher, to study the etching rate, surface morphology, material removal characteristics, and surface roughness evolution after the plasma etched removal. It is revealed that the material removal with a typical profile is achieved without introducing further damage. At the same time, the surface finish and surface integrity were enhanced by the AP plasma. The underlying mechanism of the process was investigated. Additionally, the optimized gas composition is then applied to the larger area etching by the computer-controlled scanning with different feed rates. Based on the experimental results, the surface evolution during the plasma etching process is revealed in detail. The surface removal profile also demonstrates that this method can provide an alternative way to achieve damage-free material removal for a larger area substrate by the duplicating of the typical removal profile with different etching path. Highlights: The use of atmospheric-pressure plasma for damage-free material removal on Si wafer by CCP-type plasma etcher. Material removal with a typical profile is achieved without introducing further damage. The surface finish and surface integrity were enhanced by the atmospheric-pressure plasma. Comprehensive investigation on the underlying mechanism of material removal and surface smoothing was carried out.